Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Active Learning pada Mata Pelajaran IPS Materi Bencana Alam di Kelas IV SDI Halibenaus - Yulius Amtiran (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study was motivated by the low learning outcomes of students in Social Studies, particularly on natural disaster material in Grade IV of SDI Halibenaus. The purpose of this research was to describe the implementation of the Active Learning model in improving students’ learning outcomes. This study employed a qualitative approach using Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 17 fourth-grade students consisting of 10 boys and 7 girls. Data collection techniques included observation, tests, and documentation, while data analysis was carried out through data reduction, data display, and conclusion drawing. The results indicated an improvement in students’ learning outcomes in each cycle. The average score in Cycle I was 64.35% with a mastery level of 35.29%, which increased in Cycle II to 83.17% with a mastery level of 82.35%. Based on these findings, it can be concluded that the implementation of the Active Learning model is effective in improving students’ learning outcomes in Social Studies on natural disaster material for fourth-grade students at SDI Halibenaus.